ANALISIS MANAJEMEN RESIKO ISLAM TERHADAP PENETAPAN FEE TRANSAKSI BRI LINK PADA BRI LINK UNIQ DI SENTANI - Fadli Purwanto; Fatmawati Ismail; Abdul Karman (SUAN PUBLISHER, 2025)
BRI Link Agent is one of BRI's innovative steps to improve the quality of its banking services. In this program, BRI collaborates with its own customers to act as agents who carry out banking transactions online. This study investigates BRI Link, BRI Link's advantages, requirements to become a BRI Link Agent, BRI Link agent support applications, BRI Link violation sanctions, BRI Link rights and obligations, BRI Link UNIQ transfer fee determination in Sentani. In expanding access to financial services for the community, especially in densely populated areas by BRI Link Agents. Through a qualitative approach involving in-depth interviews and secondary data analysis, this study describes various important aspects related to BRI Link agents, including the determination of BRI Link transaction fees and risk management at BRI Link Agents. However, there are transaction problems at BRI Link Agents such as replacement of nominal errors due to fraud cases on third parties, human error, network disruptions, fraud committed by consumers are still obstacles that need to be overcome. Based on the results of this study, it is recommended that BRI Link UNIQ agents in Sentani carry out risk management to minimize the risk losses that have occurred due to problems that have occurred at BRI Link agents and anticipate these problems by continuing to support and improve the BRI Link UNIQ agent ecosystem in Hinekombe Subdistrict, Sentani.